Activation of Adenosine A3 Receptor Alleviates TNF-α-Induced Inflammation through Inhibition of the NF-κB Signaling Pathway in Human Colonic Epithelial Cells - Tianhua Ren; Yumei Qiu; Weiyun Wu; Xiao Feng; Shicai Ye; Zhuang Wang; Ting Tian; Yanting He; Caiyuan Yu; Yu Zhou (Mediators of Inflammation)
To investigate the expression of adenosine A3 receptor (A3AR) in human colonic epithelial cells and the effects of A3AR activation on tumor necrosis factor alpha (TNF-α-) induced inflammation in order to determine its mechanism of action in human colonic epithelial cells, human colonic epithelial cells (HT-29 cells) were treated with different concentrations of 2-Cl-IB-MECA prior to TNF-α stimulation, followed by analysis of NF-κB signaling pathway activation and downstream IL-8 and IL-1β production. A3AR mRNA and protein were expressed in HT-29 cells and not altered by changes in TNF-α or 2-Cl-IB-MECA. Pretreatment with 2-Cl-IB-MECA prior to stimulation with TNF-α attenuated NF-κB p65 nuclear translocation as p65 protein decreased in the nucleus of cells and increased in the cytoplasm, inhibited the degradation of IκB-α, and reduced phosphorylated-IκB-α level significantly, compared to TNF-α-only-treated groups. Furthermore, 2-Cl-IB-MECA significantly decreased TNF-α-stimulated IL-8 and IL-1β mRNA expression and secretion, compared to the TNF-α-only treated group. These results confirm that A3AR is expressed in human colonic epithelial cells and demonstrate that its activation has an anti-inflammatory effect, through the inhibition of NF-κB signaling pathway, which leads to inhibition of downstream IL-8 and IL-1β expression. Therefore, A3AR activation may be a potential treatment for gut inflammatory diseases such as inflammatory bowel disease.